Dimsum Ikan Sebagai Alternatif Peluang Usaha Peningkatan Gizi Keluarga - Widiastuti, Irawati Mei; Rukka, Andi Heryanti; Ndobe, Samliok; Rizal, Achmad; Hermawan, Roni (Universitas Madako Tolitoli, 2025)
This community service activity aims to increase fish consumption as a source of quality protein by making fish-based dimsum. This activity was carried out in Tondo Village, Mantikulore District, Palu City, Central Sulawesi in 2024 involving 30 participants from various backgrounds, including housewives and teenagers. The methods used include counseling regarding nutritional needs, demonstrations of making fish dim sum, and direct practice by participants. The results of the activity showed an increase in participants' knowledge and skills in processing fish, as well as good acceptance of fish dimsum products in terms of taste and nutrition. Apart from meeting the family's nutritional needs, this activity opens up opportunities for fish-based small businesses. It is hoped that this activity can contribute to increasing fish consumption and sustainable community welfare.